Biathlon standing shooting performance, shooting technical components and postural balance at rest and during a race simulation - Köykkä, Miika (2018)
Stability of hold and postural balance have been reported to be related to standing shooting performance, and to differentiate between different experience levels of biathletes. Recently, ability to minimize the movement of the rifle during the triggering phase has been suggested to be important. Race analyses have reported men to be slightly faster in their shooting than women. The purpose of this thesis was to study factors determining biathlon standing shooting performance at rest and during a race simulation, and differences in them between genders and age groups.